Novel Therapeutic Approaches for the Treatment of Retinal Degenerative Diseases: Focus on CRISPR/Cas-Based Gene Editing - Gallego, Carmen; Gonçalves, Manuel A. F. V.; Wijnholds, Jan (Frontiers in Neuroscience, 2020)
Inherited retinal diseases encompass a highly heterogenous group of disorders caused by a wide range of genetic variants and with diverse clinical symptoms that converge in the common trait of retinal degeneration. Indeed, mutations in over 270 genes have been associated with some form of retinal degenerative phenotype. Given the immune privileged status of the eye, cell replacement and gene augmentation therapies have been envisioned. While some of these approaches, such as delivery of genes through recombinant adeno-associated viral vectors, have been successfully tested in clinical trials, not all patients will benefit from current advancements due to their underlying genotype or phenotypic traits. Gene editing arises as an alternative therapeutic strategy seeking to correct mutations at the endogenous locus and rescue normal gene expression. Hence, gene editing technologies can in principle be tailored for treating retinal degeneration. Here we provide an overview of the different gene editing strategies that are being developed to overcome the challenges imposed by the post-mitotic nature of retinal cell types. We further discuss their advantages and drawbacks as well as the hurdles for their implementation in treating retinal diseases, which include the broad range of mutations and, in some instances, the size of the affected genes. Although therapeutic gene editing is at an early stage of development, it has the potential of enriching the portfolio of personalized molecular medicines directed at treating genetic diseases.